2008
DOI: 10.1097/ccm.0b013e318183f646
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection by nitrous oxide: Facts and evidence*

Abstract: These data provide experimental evidence that nitrous oxide, which is a cost-efficient and easily available gas, has potentially neuroprotective properties in rodents when given alone at nonanesthetic concentrations. Therefore, because there is a lot at stake for the affected patients and society--in terms of easy access to treatment, profound impact of brain damage, cost of treatment, and subsequent financial cost on society--we believe that further studies should investigate thoroughly the possible potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 44 publications
6
25
0
Order By: Relevance
“…Next, in contrast to the adverse effect of intraischemic nitrous oxide and in agreement with previous reports in rats subjected to mechanical ischemia, 21,23 we found that nitrous oxide given after ischemia reduces ischemic brain damage at the cortical but not the subcortical level. Such a dichotomic effect of postischemic nitrous oxide has been attributed to the striatum (which constitutes the main part of the subcortical areas that are damaged in the MCAO ischemic model) being difficult to protect against stroke because it experiences complete blood flow cessation during ischemia because of its lack of collateral vasculature compared with the cortex.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Next, in contrast to the adverse effect of intraischemic nitrous oxide and in agreement with previous reports in rats subjected to mechanical ischemia, 21,23 we found that nitrous oxide given after ischemia reduces ischemic brain damage at the cortical but not the subcortical level. Such a dichotomic effect of postischemic nitrous oxide has been attributed to the striatum (which constitutes the main part of the subcortical areas that are damaged in the MCAO ischemic model) being difficult to protect against stroke because it experiences complete blood flow cessation during ischemia because of its lack of collateral vasculature compared with the cortex.…”
Section: Discussionsupporting
confidence: 74%
“…Brain damage was assessed 24 h after injection of NMDA or NMDA plus tPA or after the onset of ischemia for intraischemic experiments and 48 h after the onset of brain ischemia for postischemic experiments to allow "better" comparison with previous mechanical and thromboembolic studies. 23,24,29 Comparative studies using multiple staining techniques 32,33 have shown that assessment of infarct size at 24 h is a time condition sufficient to obtain consolidated infarct volumes (i.e., whose assessment would be similar if performed one or several days later), thereby allowing reliable comparison between the data obtained at 24 h or 48 h after the onset of brain ischemia. The brain was removed and frozen in isopentane.…”
Section: Assessment Of Brain Damagementioning
confidence: 99%
See 3 more Smart Citations